Crystal growth and piezoelectric properties of Ca3Ta(Ga1−x Scx)3Si2O14 single crystals. (August 2017) - Igarashi, Yu; Ohashi, Yuji; Yokota, Yuui; Arakawa, Mototaka; Inoue, Kenji; Yamaji, Akihiro; Shoji, Yasuhiro; Kamada, Kei; Kurosawa, Shunsuke; Yoshikawa, Akira
Abstract: Ca3 Ta(Ga1- x Sc x )3 Si2 O14 (CTGSS) single crystals with various Sc concentrations ( x = 0, 0.1, 0.2, 0.3, and 0.4) were grown by the micro-pulling-down method and their structure and chemical composition were evaluated. Through the powder X-ray diffraction (XRD) measurement and backscattered electron (BSE) imaging, it was demonstrated that all the CTGSS crystals with different Sc concentration were successfully grown as langasite-type structure although some secondary phases were observed for the crystals with x = 0.2, 0.3 and 0.4. Lattice parameters calculated from the powder XRD pattern generally increased with Sc substitution. Measured parameters for CTGSS crystal with x = 0.1 were larger permittivity ε 11 T / ε 0 and lower electromechanical coupling coefficient k 12 and piezoelectric constant d 11 than those for CTGS crystal with x = 0. It was also suggested that piezoelectric constant | d 14 | became larger due to the Sc substitution.